Legal Protection of Indonesian Migrant Workers to Achieve the Principles of Decent Work and Economic Growth in SDGs - Defisa; Endeh Suhartini; Nurwati (Warmadewa Press, 2025)
Poverty is a major challenge to development in Indonesia, with the number of poor people reaching 28.01 million in 2016. Economic inequality between rural and urban areas worsens the situation, so that employment opportunities, including through sending Indonesian Migrant Workers (PMI) abroad, are one of the important solutions. PMI, the majority of whom are women, contribute significantly to the country's foreign exchange through remittances of up to hundreds of trillions of rupiah per year. However, challenges such as discrimination, exploitation, violence, and limited legal protection are still serious problems. The Indonesian government has sought better protection through Law No. 18 of 2017, bilateral cooperation, and integration of decent work principles in accordance with SDG 8, which includes pre-placement education, legal protection, and international cooperation. This study employs a normative legal approach by analyzing relevant laws and regulations to evaluate their effectiveness in protecting PMI. Interviews with stakeholders, including policymakers and migrant workers, provide practical insights to complement the legal analysis. Secondary data, including statutory regulations, court decisions, and academic literature, are examined narratively to assess existing policies and their implementation. The results show that the legal protection model for PMI has not fully guaranteed their security and welfare. Regulatory revisions are needed to address the rampant cases of violence and exploitation. Implementation of the principle of decent work requires the active involvement of the government, non-governmental organizations, and destination countries. Socialization of workers' rights must be strengthened to empower migrant workers in fighting for their rights. To enhance migrant workers' safety and welfare, regulatory reforms are urgently needed to address persistent issues of violence and exploitation. Strengthening enforcement mechanisms and cross-border cooperation is crucial to ensuring legal protection. An integrated policy approach that involves government, civil society, and international stakeholders is imperative to create a more effective protection framework and maximize PMI's contributions to national development.